2009
DOI: 10.1002/biot.200800213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recombinant anthrax vaccine against Bacillus anthracis aerosol spore challenge: Preclinical evaluation in rabbits and Rhesus monkeys

Abstract: This report describes the immunogenicity and protective efficacy of Escherichia coli-expressed recombinant protective antigen (rPA) in New Zealand White rabbits and Rhesus Macaques against an aerosol challenge with Bacillus anthracis spores (IVRI strain, tox+cap+). A dose-ranging study was performed in which it became evident that the level of anti-PA IgG and toxin-neutralizing antibody titer was directly proportional to the dose of rPA administered. However, the onset time of primary and secondary immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, this response addresses both toxaemia and the bacteremia, which are both associated with B. anthracis infection. Of note, full-protection of rabbits vaccinated with a PA sub-unit vaccine correlates with at least 3-fold higher levels of neutralizing antibodies 39 40 compared to the antibodies in the fully protected animals following SterneΔ htrA vaccination. Similarly, in the guinea pig immunization experiments ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, this response addresses both toxaemia and the bacteremia, which are both associated with B. anthracis infection. Of note, full-protection of rabbits vaccinated with a PA sub-unit vaccine correlates with at least 3-fold higher levels of neutralizing antibodies 39 40 compared to the antibodies in the fully protected animals following SterneΔ htrA vaccination. Similarly, in the guinea pig immunization experiments ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Both vaccines rely largely on the protection afforded by immunological responses against the PA protein [14–20]. Many studies have shown the protective efficacy of PA based anthrax vaccines in several animal genera and species including guinea pigs [21–25], rabbits [2629] and NHPs [20, 26, 3033]. A few studies have gone further to evaluate correlate of protection levels based on antibody to PA for AVA in rabbits [28, 29] and for rPA in rabbits [27] and guinea pigs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as a single, well-defined, recombinant protein, rPA represents an attractive antigen alternative to that found in AVA, which while containing predominantly PA absorbed to alum, also contains other antigens and is of undefined composition with lot to lot variation (38). A number of studies in monkeys, a suitable surrogate for predicting the human anthrax vaccine response (39), have shown complete protection against lethal aerosolized anthrax challenge following a 2–3 immunization regimen of AVA or rPA on alum (3942), but complete protection following a single immunization has yet to be demonstrated in these animals. Thus, the ability of CpG-ODN to promote rapid, high titer and durable antibody responses to antigens makes this class of adjuvant a strong candidate for improving the rapidity and magnitude of antibody responses to vaccines against potential biological warfare agents such as anthrax.…”
Section: Discussionmentioning
confidence: 99%